Evaluation of Salivary and Serum Antioxidant and Oxidative Stress Statuses in Patients with Chronic Periodontitis: A Case-Control Study - Ahmadi-Motamayel, Fatemeh; Goodarzi, Mohammad T.; Jamshidi, Zohreh; Kebriaei, Reza (Frontiers in Physiology, 2017)
Aim: Local bacteria stimulate polymorphonuclear neutrophils to release reactive oxygen species in periodontitis. Increased levels of oxidative stress play a significant role in the pathogenesis of periodontitis. Therefore, this study aimed to evaluate total salivary and serum antioxidant capacity and malondialdehyde in patients with chronic periodontitis. Materials and methods: Fifty-five healthy subjects and 55 patients with chronic periodontitis, with an age range of 30–50 years, were evaluated. After clinical examination and case selection, unstimulated whole saliva was collected in the morning. Blood samples were taken from the antecubital vein. Total antioxidant capacity and malondialdehyde levels were evaluated by spectrophotometric assay. Data were analyzed with t-test, using Stata.11 software program. Results: The periodontitis group exhibited lower salivary (0.16) and serum (0.36) total antioxidant capacity (P = 0.11) compared to the control group. Mean salivary malondialdehyde levels in the case and control groups were 0.80 ± 0.09 and 0.42 ± 0.08, respectively. The results showed significantly higher levels of salivary and serum malondialdehyde in the periodontitis group. Gender did not have any effect on antioxidant and oxidative stress levels. Conclusion: This study indicated increased levels of salivary and serum oxidative stresses in patients with chronic periodontitis. Total antioxidant capacity was mildly lower in the saliva and serum of these patients. Higher malondialdehyde levels with no changes in antioxidant status can result in systemic and local complications in these patients.